(3MGTjI Ydi TQM GddeYIs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B... (3cJGH GdRcGI hgj GSe Ydi aYdg cGdUObI hbGd GdeUfa aj GdTQM hGdOQhS GdHjGf Cfg eUOQ (B... (3heYfGgG aj GdCUd Gdfeh hGdWgGQI hGdUdGM haj GdTQY (B.. (3GNQGL TjA ef GdeGd Ydi GdWQjb GdeYghO Ch Pdc (B...s
(3BNQgG (B:s
... (3hEf bdfG dG jdRe hGMOG efgeG dGfg dG Odjd Ydjg dGfg djS HMQ ajdReg Mce faSg hdG gh eedhc dGfg JMQjQ efg LRA hG gh ef YjdhdI ehdGg ajdReg aWQJg decGf (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis